Pengembangan Learning Management System Berbasis Moodle pada Kompetensi Dasar Perawatan Sistem Continuously Variable Transmission - Janah, Lulu’ul; Kurniawan, Adhetya (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study aims to develop a Learning Management System based on Moodle to improve students' learning outcomes on CVT system materials. The method used in this study is a research and development method with the ADDIE (Analyze, Design, Development, Implementation, and Evaluation) model and uses a one group pretest-posttest design. The research subjects are Class XI TBSM 3 students of SMK Texmaco Pemalang which totals 38 students. The results of the feasibility test from media experts got 82.5% results and the results of the feasibility test from material experts got a result of 96.25% with the category of